2014
DOI: 10.1074/jbc.m114.553644
|View full text |Cite
|
Sign up to set email alerts
|

The Specific Monomer/Dimer Equilibrium of the Corticotropin-releasing Factor Receptor Type 1 Is Established in the Endoplasmic Reticulum

Abstract: Background: GPCRs may be expressed in a monomer/dimer equilibrium at the plasma membrane. Results: For the dimeric CRF 1 R, we found a constant monomer/dimer equilibrium not only at the plasma membrane but also in the ER. Conclusion:The monomer/dimer equilibrium of the CRF 1 R is established already in the ER. Significance: Our findings shed new light on the monomer/dimer equilibrium of GPCRs and on ER functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…Furthermore, the GPCR-GPCR interfaces are most likely to be of dynamic character (Hu et al 2013). GPCRs were described to be potentially expressed as a mixture of monomers and homomers, and the two forms were found to interconvert dynamically in an equilibrium ((Hern et al 2010, Kasai et al 2011, Calebiro et al 2013, Teichmann et al 2014, reviewed in Lambert 2010).…”
Section: What Do We Know About Interactions Between Gpcr Protomers Comentioning
confidence: 99%
“…Furthermore, the GPCR-GPCR interfaces are most likely to be of dynamic character (Hu et al 2013). GPCRs were described to be potentially expressed as a mixture of monomers and homomers, and the two forms were found to interconvert dynamically in an equilibrium ((Hern et al 2010, Kasai et al 2011, Calebiro et al 2013, Teichmann et al 2014, reviewed in Lambert 2010).…”
Section: What Do We Know About Interactions Between Gpcr Protomers Comentioning
confidence: 99%
“…These combined techniques suggest the existence of native serotonin 5-HT 2C receptor homomeric complexes in the apical membrane of living choroid plexus epithelial cells (Herrick-Davis et al, 2015). For some class A and B GPCRs, an equilibrium between monomeric and possible dimeric species was found, with a low proportion of dimers, by using fluorescence crosscorrelation spectroscopy (Teichmann et al, 2014), a development of FCS for dual-color applications that allows discrimination of single-labeled entities carrying two different fluorophores from the duallabeled diffusing particles resulting from their interaction. In this approach, the emission of the two fluorophores are separately registered by two different detectors, and when the two differently labeled partners comigrate, the fluctuations in the intensity of the two fluorophores will correlate as they diffuse into and out of the observation volume together.…”
Section: Introductionmentioning
confidence: 99%
“…The crosscorrelation function provides more sensitive information than the diffusion coefficient alone for the detection of interactions. The information gathered in the work of Teichmann et al (2014) confirmed single molecule total internal reflection fluorescence microscopy (TIRFM) studies at b 1 -AR or M 1 muscarinic acetylcholine receptors (M 1 Rs) (Hern et al, 2010;Calebiro et al, 2013). However, a homogeneous population of dimers without evidence of the coexistence of the monomeric species in equilibrium was found in the case of serotonin 5-HT 2C and also b 1 -AR or M 1 R in other FCS/photon-counting histogram-based studies (HerrickDavis et al, 2012(HerrickDavis et al, , 2013(HerrickDavis et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although recent studies have used direct methods with near single-molecule sensitivity, such as total internal reflection fluorescence (Calebiro et al, 2013;Kasai and Kusumi, 2014;Teichmann et al, 2014) and fluorescence correlation spectroscopy (FCS) (Briddon et al, 2008;Malengo et al, 2008;Ganguly and Chattopadhyay, 2010;Herrick-Davis et al, 2012Corriden et al, 2014), these studies were performed using recombinant cell lines. The purpose of the present study was to determine the monomer/oligomer status of a native GPCR endogenously expressed in its natural cellular environment.…”
Section: Introductionmentioning
confidence: 99%